MgCl2 center dot 6CH(3)OH: a simple molecular adduct and its influence as a porous support for olefin polymerization - Gnanakumar, Edwin S.; Gowda, Ravikumar R.; Kunjir, Shrikant; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Chakraborty, Debashis; Gopinath, Chinnakonda S. (ACS Catalysis, 2013)
A single phase molecular adduct, MgCl2 center dot 6CH(3)OH has been synthesized using MgCl2 and the simplest alcohol, methanol. Structural, spectroscopic, and morphological studies have been carried out for a better understanding of the single phase MgCl2 center dot 6CH(3)OH adduct. C-13 CPMAS solid state NMR studies show all six methanol molecules are magnetically equivalent and present in a single environment around the Mg2+ center. Raman spectral analysis of the characteristic peak at 708 cm(-1) substantiates octahedral coordination of six CH3OH molecules around Mg2+. Solid state C-13 NMR measurements, made after heat treatment at different temperatures, have been utilized to understand the variations in CH3OH stoichiometry and coordination around Mg2+ with temperature. A titanated active catalyst, TiCl4 on MgCl2 center dot 6CH(3)OH, has also been synthesized and subjected to detailed characterizations. The active catalyst shows high surface area (102 m(2)/g) and mesoporosity. The titanated catalyst has been screened for ethylene polymerization reactions using different cocatalysts (R3Al; R= -CH3, -CH2CH3, and -CH2CH(CH3)(2)). A total of 7.25 kg of polyethylene per gram of catalyst has been obtained with Me3Al cocatalyst, which is six times higher in activity compared with commercial Me3Al/TiCl4/MgCl2 center dot 6EtOH-supported orted catalystAlthough porosity influences the catalytic activity, other factors also seem to contribute to the total catalytic activity.
Keywords: heterogeneous catalysis; MgCl2; Molecular adduct; olefin polymerization; Ziegler-Natta catalyst

9-Fluorenemethanol: an internal electron donor to fine tune olefin polymerization activity - Gnanakumar, Edwin S.; Chokkapu, Eswara Rao; Kunjir, Shrikant; Ajithkumar, Thalasseril G.; Rajamohanan, P. R.; Chakraborty, Debashis; Gopinath, Chinnakonda S. (Dalton Transactions, 2014)
A new MgCl2 based molecular adduct has been synthesized with 9-fluorenemethanol (9FM) as a novel internal electron donor (IED), along with ethanol (EtOH) (MgCl2 center dot n9FM center dot xEtOH). The above molecular adduct has been subjected to a variety of structural, spectroscopic and morphological characterization techniques. The results of the solid state C-13 CPMAS NMR technique suggests the coordination of 9FM to MgCl2. Observation of a low angle diffraction peak at 2 theta = 5.7 degrees (d = 15.5 angstrom) underscores the coordination of 9FM along the z-axis, and ethanol in the molecular adduct. Active Ziegler-Natta catalysts were prepared by two different synthesis methods; the conventional method to obtain a high surface area active catalyst, and other one with 9FM as an integral part of the active catalyst in order to study the influence of 9FM as an IED over the active sites. The active catalysts were also characterized thoroughly with different analytical tools. The XRD results show (003) facets of delta-MgCl2 (alpha-MgCl2) for the conventional (non-conventional) titanated catalyst. Results of the ethylene polymerization activity study reveals that the conventionally prepared highly porous active catalyst shows 1.7-2.5 times higher activity than the non-conventional prepared catalyst; however, the latter shows a low molecular weight distribution and confirms the role of the Lewis base as an IED.

Unexpected observations during the total synthesis of calothrixin B-sodium methoxide as a source of hydride - Bhosale, Shrikar M.; Momin, Aadil A.; Kunjir, Shrikant; Rajamohanan, P. R.; Kusurkar, Radhika S. (Tetrahedron Letters, 2014)
During the total synthesis of calothrixin B, various novel and unexpected results were noticed such as cleavage of C-N bond in imine using sodium cyanoborohydride, sodium methoxide as a hydride source for reduction, deformylation in the presence of bromine, and deacylation using ceric ammonium nitrate (CAN). A detailed mechanism has been proposed for the unexpected results and a few of them are generalized. Temperature dependent NMR studies have been carried out for confirmation of the structure of one of the intermediates in the synthetic sequence. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Azoxybenzene; Calothrixin B; reduction; Sodium cyanoborohydride; Sodium methoxide